Empowering traditional heritage through angklung musical instruments: a case study in Malaysia - Muhammad Asyraf Mohd Bakri; Siti Suhaily Surip; Kamal Sabran; Nurul Fazita Mohammad Rawi (Penerbit Universiti Kebangsaan Malaysia, 2021)
Angklung is a traditional musical heritage musical instrument originating in Indonesia, but around the 1930s, angklung began to take root and was performed by the people of Ponorogo from the West Java Islands in Johor, Malaysia. Angklung is used in conjunction with horse dance for some formal events. In addition, only certain species of bamboo are used in the production of angklung. However, angklung musical instruments are still less played, just a formal program compared to other modern musical instruments. If examined in more depth, angklung musical instruments are able to produce pop songs, ballads, dangdut, jazz, traditional rhythms, and much more. There are two objectives to this study. The first objective is to identify the causes of angklung that have no place in society today. The second objective is to analyze and summarize the findings of the study. The method of this study uses content analysis through; websites, articles, theses, and newspapers for scientific information. The findings of this study found a lack of hereditary heritage of angklung production and game in Malaysia. This study can track the development of angklung musical instruments in Malaysia. In conclusion, angklung musical instruments are still accepted by the community but there are obstacles from the materials and makers of angklung.